2017
DOI: 10.3390/e19110592
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Optimization of Agricultural Land Use Based on Cross-Entropy Method

Abstract: An integrated optimization model was developed for the spatial distribution of agricultural crops in order to efficiently utilize agricultural water and land resources simultaneously. The model is based on the spatial distribution of crop suitability, spatial distribution of population density, and agricultural land use data. Multi-source remote sensing data are combined with constraints of optimal crop area, which are obtained from agricultural cropping pattern optimization model. Using the middle reaches of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…(Masoomi et al, 2012). In particular, it has been used in facility location problems (Church, 2002;Liu and Kao, 2010;Kratika et al, 2014;Eiselt and Marianov, 2015), ecological conservation models (Williams and ReVelle, 1996;Snyder et al, 2004;Costello and Polansky, 2004;Billionnet, 2013;Shao et al, 2015;Beyer et al, 2016;), suitability of land for agricultural use (Henseler et al, 2009;Hao et al, 2017), and regionalization problems and p-compact regions (Li et al, 2014;Kim et al, 2015).…”
Section: Optimization and Land Use Allocationmentioning
confidence: 99%
“…(Masoomi et al, 2012). In particular, it has been used in facility location problems (Church, 2002;Liu and Kao, 2010;Kratika et al, 2014;Eiselt and Marianov, 2015), ecological conservation models (Williams and ReVelle, 1996;Snyder et al, 2004;Costello and Polansky, 2004;Billionnet, 2013;Shao et al, 2015;Beyer et al, 2016;), suitability of land for agricultural use (Henseler et al, 2009;Hao et al, 2017), and regionalization problems and p-compact regions (Li et al, 2014;Kim et al, 2015).…”
Section: Optimization and Land Use Allocationmentioning
confidence: 99%
“…A number of research paper have been published globally to identify the fate of groundwater contamination using arti cial neural network (Wagh et al, 2016), multivariate statistics (Gharbi et al, 2019), fuzzy-TOPSIS (Kim et al,2013), entropy method for agricultural land use (Hao et al,2017), analytic hierarchy process (Okada et al,2008), TOPSIS based on informative weight and ranking . Peiyue et al, (2011) studied the drivers of hydrogeochemical evolution assessment and mechanisms of groundwater quality using the TOPSIS method for Pengyang county NW China and observed that the groundwater is t for human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of matching the data obtained by calculations or modeling to the real states of complex systems is that most of the complexity is considered in terms of dimensionality or structural properties of the studied objects. As the experience of modern monitoring (informationanalytical) systems related to the study of complex objects, such as different in the hierarchy of ecological systems [1][2][3][4], the complexity is generally appropriate to consider with the peculiarities of the interaction of such an object with the environment, which consists of systems set of different nature, in direct or indirect contact with the components and elements of such an object. The study of such system objects is based on the accuracy of their model representation and the clarity of the definition of the target position for structuring as a complex complex of cooperative nature, ie independent functioning systems structurally linked to achieve this goal.…”
Section: Introductionmentioning
confidence: 99%